A comparative filling materials study on microstructure and mechanical properties of welded joints of dissimilar Al–Mg–Si alloys using CMT-laser beam oscillation hybrid welding - H.Y. Shen; J.M. Yu; L. Wang; F. Vogel; C.J. Li; H. Nagaumi (Journal of Materials Research and Technology)
This study aims to examine the effects of ER4047 and ER5183 filler materials on the microstructure and mechanical properties of joints welded between 6061 aluminum alloy and a newly developed 6xxx series aluminum alloy. The welding process was conducted using an emerging CMT-laser beam oscillation hybrid welding technique and joints performance was assessed through microstructural characterization, porosity analysis, and mechanical testing. The results demonstrate that the Si-rich ER4047 filler significantly enhances molten pool flowability and thermal conductivity, reducing porosity to 0.32%, compared to 0.46% for the Mg-rich ER5183 filler. Microstructural analysis revealed a distinct layered structure on the 6061 side, contributing to a hard-soft microstructural configuration that enhances ductility, with fracture strains of 3.4% for ER4047 and 4.8% for ER5183. In this study, turbulent flow dominates over previously proposed laminar flow, but a prolonged duration for complete solute mixing is still required, leading to the persistent presence of unmixed and partially mixed zones in the liquid weld pool before solidification. The fine equiaxed grain zone observed on the new 6xxx side was attributed to local constitutional supercooling and the presence of abundant nucleation sites. Strength predictions indicate that solution strengthening is a significant contributor, with values of 50.87 for ER4047 and 31.54 for ER5183, highlighting the critical role of Si as a strengthening agent. While the ER4047 joint exhibited higher predicted strength, it is imperative to address its porosity improvement to mitigate the risk of crack initiation. In contrast, the ER5183 joint demonstrated superior tensile strength (226.76 MPa) and lower crack sensitivity, rendering it more suitable for high-performance structural applications. Our findings provide novel insights into optimizing filler materials and welding techniques for high-strength aluminum alloy joints.